Analisis Kesulitan Membaca di Kelas Rendah - Aflah Husnaini Matondang; Bintang Mahrani Abdullah; Friska Widia; Novia Ramadani; Windi Melisa (Universitas Palangka Raya, 2023)
Difficulty reading in the lower grades of elementary school is a common problem faced by a number of students. The process of learning to read at this early stage is an important foundation for their future literacy development. Some factors that can affect reading difficulties include intelligence, physical health, sensory abilities, interests, family environment, motivation. In dealing with reading difficulties in the lower grades of elementary school, a holistic and diverse approach is needed. Teachers need to use learning methods that integrate vocabulary understanding, and student interests. In addition, involving parents in providing support and creating an environment that supports reading at home is also important. With the right approach and collaborative effort, students can overcome their reading difficulties and improve their literacy skills. This study aims to understand in depth the factors that cause reading difficulties in the lower grades of elementary school. This article uses a literature study to collect data which is carried out using literary literacy. Methods of data collection using various theoretical references in the field of reading difficulties in low grades related to research. The data sources in this study are in the form of books, journals, research report articles, and internet sites.